Establishment and characterization of an immortalized red river hog blood-derived macrophage cell line - Takenouchi, Takato; Masujin, Kentaro; Ikeda, Rina; Haraguchi, Seiki; Suzuki, Shunichi; Uenishi, Hirohide; Onda, Eiji; Kokuho, Takehiro (Frontiers in Immunology, 2024)
Red river hogs (RRHs) (Potamochoerus porcus), a wild species of Suidae living in Africa with a major distribution in the Guinean and Congolian forests, are natural reservoirs of African swine fever virus (ASFV) and typically are asymptomatic. Since blood and tissue macrophages of suid animals are target cell lineages of ASFV, RRH-derived macrophages are expected to play an important role in suppressing disease development in infected individuals. In the present study, we successfully isolated RRH-derived blood macrophages using co-culture techniques of RRH blood cells with porcine kidneyderived feeder cells and immortalized them by transferring SV40 large T antigen and porcine telomerase reverse transcriptase genes. The newly established macrophage cell line of the RRH-derived blood cell origin (RZJ/IBM) exhibited an Iba1-, CD172a-, and CD203a-positive typical macrophage-like phenotype and up-regulated the phosphorylation of nuclear factor-kB p65 subunit and p38 mitogen-activated protein kinase in response to the bacterial cell wall components, lipopolysaccharide (LPS) and muramyl dipeptide. In addition, RZJ/IBM cells produced the precursor form of interleukin (IL)-1b and IL-18 upon a stimulation with LPS, leading to the conversion of IL-18, but not IL-1b, into the mature form. Time-lapse live cell imaging with pHrodo dye-conjugated Escherichia coli BioParticles demonstrated the phagocytotic activity of RZJ/IBM cells. It is important to note that RZJ/IBM cells are clearly susceptible to ASFV infection and support viral replication in vitro. Therefore, the RZJ/IBM cell line provides a unique model for investigating the pathogenesis of ASFV.